Univariate and multivariate linear relationships among traits in sunflower cultivation (Acta Scientiarum. Agronomy, 2025)
Evaluating characteristics in sunflower cultivation through univariate and multivariate selection of agronomic traits and grain yield helps choose cultivars and hybrids, and supports crop breeding studies. Yet, the scientific literature relies on data from limited cultivation environments, potentially undermining result reliability. In this context, this study aimed to evaluate the linear relationships among morphological traits of sunflower in a low-altitude subtropical environment and identify traits that can assist in the indirect selection of cultivars, hybrids, and genotypes in field trials of the national sunflower genotype evaluation network. Data from five experimental years conducted annually between 2017/2018 and 2022/2023 were used. The experiments were conducted at the Federal University of Santa Maria (UFSM). The experimental design consisted of randomized blocks with four replications, considering 34 treatments (genotypes) evaluated over five experimental years, totaling 1,754 plants evaluated during the period. The evaluated traits were plant height (cm), capitulum diameter (cm), thousand-achene mass (g), number of achenes per capitulum, and individual achene yield per plant (g). Subsequently, the relationship among traits was investigated using Pearson correlation (r) and path (cause and effect) analyses. The traits number of achenes per capitulum, thousand-achene mass, and capitulum diameter are positively related. The magnitude of Pearson correlations among evaluated traits changes in an environment with prolonged water deficit conditions. The number of achenes per capitulum and thousand-achene mass have a linear relationship and a direct effect on individual achene yield. Capitulum diameter has a direct effect on the number of achenes per capitulum and can be used to assist in the indirect selection of sunflower genotypes, hybrids, and cultivars.